2010
DOI: 10.1038/nature08738
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cells derive directly from aortic endothelium during development

Abstract: A major goal of regenerative medicine is to instruct formation of multipotent, tissue-specific stem cells from induced pluripotent stem cells (iPSCs) for cell replacement therapies. Generation of hematopoietic stem cells (HSCs) from iPSCs or embryonic stem cells (ESCs) is not currently possible, however, necessitating a better understanding of how HSCs normally arise during embryonic development. We previously showed that hematopoiesis occurs through four distinct waves during zebrafish development, with HSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
963
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 938 publications
(987 citation statements)
references
References 27 publications
18
963
0
6
Order By: Relevance
“…Interestingly, activation of PKA results in up-regulation of Foxc2, which has been recently identified to play a role in the hemogenic endothelium (Jang et al, 2015). The endothelial-tohematopoietic transition has garnered recent interest because lineage tracing and live-imaging studies have shown that HSCs emerge from the VE-cadherin + vascular endothelium in the AGM (Chen et al, 2009;Bertrand et al, 2010;Boisset et al, 2010). Efforts to understand this phenomenon in humans have culminated in various protocols for ESC differentiation (Kennedy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activation of PKA results in up-regulation of Foxc2, which has been recently identified to play a role in the hemogenic endothelium (Jang et al, 2015). The endothelial-tohematopoietic transition has garnered recent interest because lineage tracing and live-imaging studies have shown that HSCs emerge from the VE-cadherin + vascular endothelium in the AGM (Chen et al, 2009;Bertrand et al, 2010;Boisset et al, 2010). Efforts to understand this phenomenon in humans have culminated in various protocols for ESC differentiation (Kennedy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, lineage-tracing studies in which Cre recombinase was expressed under the regulatory control of the endothelial marker VE-Cadherin (VECadh) lent further support to this model [27,28]. Arguably, the strongest support for an endothelial origin of hematopoietic cells came from the recent time-lapse imaging studies that visualized the transition of endothelium into blood in real-time, both in vitro [29] and in/ex vivo [30][31][32][33]. The process of endothelial cells taking on a hematopoietic fate has been termed the endothelial-to-hematopoietic transition (EHT), and involves the bending out and rounding up of an endothelial cell and its subsequent detachment from the vascular wall and formation of a free-moving hematopoietic cell [30].…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…Insights into intrinsic regulators have come from genetic and lineage tracing studies, described below. In addition, live cell imaging of the dorsal aorta demonstrated that EHT is accompanied by dramatic changes in cell morphology, with cells initially maintaining contact with their neighbors to ensure continuity of the endothelial cell layer [30][31][32], giving cues to the molecular pathways likely to be involved in this transition. Sheer stress caused by blood flow was shown to affect the development of the hematopoietic system, at least in part through nitric oxide signaling which induces Runx1 expression in the endothelium [71,72] and reviewed in [21].…”
Section: The Microenvironment Supporting Ehtmentioning
confidence: 99%
“…The rps29 mutant has decreased HSC markers runx and myb at 36 hours post fertilization (hpf) in the aorta gonad mesonephros (AGM) region. At this stage of development, definitive HSCs emerge from the hemogenic endothelium lining the aorta[21]. Thus, endothelial cell fate specification, vasculogenesis, and the establishment of artery identity are all required for HSC formation.…”
Section: Introductionmentioning
confidence: 99%